Handling of Truant School Children by the Civil Service Police Unit (Satpol PP) (Case Study of Satpol PP Pekanbaru) - Rezi Aznan Shabila; Muhammad Zulherawan (Penerbit Yayasan Daarul Huda Kruengmane, 2026)
The handling procedures carried out by the Civil Service Police Unit (Satpol PP) of Pekanbaru City toward school students who skip classes outside school during study hours are reflected in data from a raid in October 2025, which netted 31 students from various secondary schools in Pekanbaru City. This study uses a qualitative approach with a case study method, where data were collected through in-depth interviews with 11 informants consisting of Satpol PP officers, guidance and counseling teachers, vice principals, students caught in the raid, and community figures. Data analysis applies the crime prevention strategy theory of Tonry and Farrington (1995), which divides prevention into three levels: primary, secondary, and tertiary. The results show that Satpol PP has implemented handling procedures based on Regional Regulation Number 13 of 2021, including intelligence monitoring, field security operations, data collection, in-office counseling, summoning parents, and handing students back to schools using a persuasive and humane approach. However, several weaknesses were identified, including a weak field verification mechanism that led to some innocent students being caught in the raid, minimal effective coordination between Satpol PP and schools, suboptimal primary and secondary prevention due to a predominantly reactive approach, and deterrent effects that are not yet fully sustainable. Schools, in contrast, have proven more effective in prevention through digital attendance systems, routine counseling, and daily communication with parents. This study recommends strengthening inter-agency coordination, improving field verification procedures, and developing more structured and sustainable primary prevention programs.